PENGARUH KONSENTRASI EKSTRAK KENTAL DAUN KANYERE (BRIDELIA MONOICA (L). MERR) SEBAGAI ANTIINFLAMASI DALAM SEDIAAN GEL LUKA BAKAR - Rinawati Rinawati; Irsa Tirta; Budiarti Budiarti; Dirga Aulia Eka Putri; Ika Kurniaty (Jurnal Teknologi, 2022)
Kanyere (Bridelia Monoica Merr) leaf can be used as burn medicine because they contain anti-inflammatory compounds: flavonoids, phenols, alkaloids, and tannins. Maceration is used as an extraction method to obtain kanyere leaf extract. The purpose of this study is to determine and analyze the most optimum concentration of kanyere leaf extract in curing test animals by applying kanyere leaf as a burn gel medicine with variations in the concentration of kanyere leaf extract. The method used is an in-vivo anti-inflammatory test method on 25 white rats (Rattus Novergicus) Wistar strain. Each rat was divided into 5 groups for concentration variation and positive control. Mice were coded K1, K2, K3, K4, and K5. Group K1 was smeared with gel base with 0% concentration, K2 (positive control) was smeared with brand X burn medication, while groups K3, K4, and K5 were smeared with gel base with concentrations of 2%, 4%, and 8%. The smearing of all treatment groups was carried out evenly once every morning as much as 0.1 gram for one application and then observed and measured the area of wound closure for 14 days, then the data were processed statistically. From the results of the study, was found that the percentage reduction in the area of K1 -30.38%; K2 43.21%;  K3 12.38%; K4 18.87% and K5 27.21%. The effect of Gel 8% Extract concentration on inflammation is quite significant, marked by a decrease in a burn area, but physiologically comparable to positive control although the percentage is not close enough. Meanwhile, for Gel with 2% and 4% extract,  the effect on inflammation was not maximal.